Effects of seasonality and environmental gradients on Spartina alterniflora allometry and primary production. Issue 22 (16th October 2017) - Hill, Troy D.; Roberts, Brian J.
Abstract: Predictions of how salt marsh primary production and carbon storage will respond to environmental change can be improved through detailed datasets documenting responses to real‐world environmental variation. To address a shortage of detailed studies of natural variation, we examined drivers of Spartina alterniflora stem allometry and productivity in seven marshes across three regions in southern Louisiana. Live‐stem allometry varied spatially and seasonally, generally with short stems weighing more (and tall stems weighing less) in the summer and fall, differences that persist even after correcting for flowering. Strong predictive relationships exist between allometry parameters representing emergent stem mass and mass accumulation rates, suggesting that S. alterniflora populations navigate a trade‐off between larger mass at emergence and faster rates of biomass accumulation. Aboveground production and belowground production were calculated using five and four approaches, respectively. End‐of‐season aboveground biomass was a poor proxy for increment‐based production measures. Aboveground production (Smalley) ranged from 390 to 3, 350 g m −2 year −1 across all marshes and years. Belowground production (max–min) was on average three times higher than aboveground; total production ranged from 1, 400 to 8, 500 g m −2 year −1 . Above‐ and belowground production were both positively correlated with dissolved nutrient concentrations and negatively correlated to salinity. Synthesis: Interannual variation in water quality is sufficient to drive above‐ and belowground productivity. The positive relationship between nutrients and belowground production indicates that inputs of nutrients and freshwater may increase salt marsh carbon storage and ecosystem resilience to sea level rise. Abstract : We examine drivers of salt marsh allometry and productivity using 3 years of Spartina alterniflora stem allometry, productivity, and water quality data collected from seven marshes in southern Louisiana. We found strong spatial and seasonal variation in live‐stem allometry, with short stems weighing more and tall stems weighing less in the summer and fall, variation that has important implications for nondestructive research protocols. Above‐ and belowground production increased with dissolved nutrient concentrations and declined with salinity, suggesting that freshwater inputs and nutrients can increase marsh resilience to inundation and habitat loss.